Agricultural Cooperatives in Mental Health: Farmers' Perspectives on Potential Influence. Issue 2 (3rd April 2022) - Liang, Yanni; Janssen, Brandi; Casteel, Carri; Nonnenmann, Matthew; Rohlman, Diane S.
ABSTRACT: Agricultural cooperatives are formed to promote farmers' economic, social, and legislative interests. Their role in influencing mental health is less known. We characterized farmers' experiences with cooperatives and identified the potential impact of cooperatives in promoting mental health. Semi-structured interviews were conducted in Wisconsin with 12 participants, including farmers, cooperative professionals, and agricultural extension educators. Participants were asked about stress among farmers; cooperative structures and services provided to farmers, and farmers' interactions with the cooperatives; and the role cooperatives play in reducing stress among farmers. Three main themes were developed: stress farmers were experiencing, available resources from cooperatives, and the role of cooperatives in promoting farmers' mental health. Stress farmers were experiencing was elucidated through the subthemes: increased stress, depression, and suicide and stressors involving finances, occupational pressure, relationships, isolation, and loneliness. Available resources from cooperatives were described in subthemes: cooperative characteristics, services, and engagement activities. The role of cooperatives in promoting farmers' mental health was discussed through subthemes: responder, community, facilitator, and divergent views on whether co-ops can protect farmers' mental health. Cooperatives provide members market stability, services, and opportunities for decision-making, social interaction, and civic engagement. These resources create a community where farmers feel a sense of belonging and retain a level of control. As rural communities continue to struggle with mental health resource shortages, identifying and evaluating community-based resources such as those offered by the cooperatives is imperative.